THE SYNTAX ANALYSIS OF ADVERB OF MANNER FOUND IN THE NOVEL “HUNGRY FOR YOU” - Wirawan, I Gede Nika; Juliarta, I Made (International Journal of English Learning and Applied Linguistics (IJELAL), 2024)
This research paper entitles “The Syntax Analysis of Adverb of Manner Found in the Novel “Hungry for You”. This research study analyzes the form of adverb of manner and its positions of adverb of manner found in the clause and sentence structure. This research study used the theory that was proposed by Brown and Miller (1991) and it was supported by other theories in analyzing the form and the position in adverb of manner found in the sentence structure. The method that was used to get the data was qualitative method in library research. The data were taken from the novel entitled “Hungry for You” that was written by Lynsay Sands. The result of the research suggests that there were one form of adverb of manner found in the novel entitled “Hungry for You”. They were adverb of manner that could be filled in the sentence structure in the form of adverb of manner and prepositional phrase. Suffix –ly was added to the positive form of the adjective. The form of adverb of manner can be in the prepositional phrase which was characterized by a preposition as the head of adverbial.